2023
DOI: 10.1093/cid/ciad060
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Clinical Severity, and Seasonality of Adenovirus 40/41, Astrovirus, Sapovirus, and Rotavirus Among Young Children With Moderate-to-Severe Diarrhea: Results From the Vaccine Impact on Diarrhea in Africa (VIDA) Study

Abstract: Background While rotavirus causes severe diarrheal disease in children aged <5 years, data on other viral causes in sub-Saharan Africa are limited. Methods In the Vaccine Impact on Diarrhea in Africa study (2015–2018), we analyzed stool from children aged 0–59 months with moderate-to-severe diarrhea (MSD) and without diarrhea (controls) in Kenya, Mali, and The Gambia using quantitative polymerase chain reaction. We der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Also, astrovirus infection has been associated with encephalitis and meningitis in immunocompromised patients ( Vu et al, 2017 ) and astrovirus infection has been shown to be present in the brains of some mammals ( Chae et al, 2023 ). According to several studies ( Resque et al, 2007 ; Meyer et al, 2015 ; Keita et al, 2023 ), the prevalence of astroviruses among human populations ranges from 2% to 9% at any given time. In developing countries, this percentage can be significantly higher, affecting up to 30% of the population ( De Benedictis et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, astrovirus infection has been associated with encephalitis and meningitis in immunocompromised patients ( Vu et al, 2017 ) and astrovirus infection has been shown to be present in the brains of some mammals ( Chae et al, 2023 ). According to several studies ( Resque et al, 2007 ; Meyer et al, 2015 ; Keita et al, 2023 ), the prevalence of astroviruses among human populations ranges from 2% to 9% at any given time. In developing countries, this percentage can be significantly higher, affecting up to 30% of the population ( De Benedictis et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite having a very important impact on human health, oral rotavirus (RV) vaccines need improvement [ 1 ], especially in developing countries where they underperform and where RV diarrhea represents a high burden of disease [ 2 , 3 ]. In these settings, protective immune responses against pathogens are influenced, amongst other factors, by malnutrition and chronic gut inflammation (associated with microbial dysbiosis) that manifest as environmental enteric dysfunction (EED).…”
Section: Introductionmentioning
confidence: 99%